Analisis Pengelolaan Wakaf Produktif Terhadap Kesejahteraan Masyarakat Kecamatan Mersam Kabupaten Batang Hari : Studi Pada Kelurahan Kembang Paseban - Neti Febriyanti; Youdhi Prayogo; M. Maulana Hamzah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This thesis discusses the analysis of productive waqf management on the welfare of the people of Mersam sub-district, Batanng Hari district (study in Kembang Paseban sub-district). This research aims to analyze productive waqf management on community welfare. This research is a type of descriptive qualitative research. The location of this research is in the Kembang Paseban sub-district, Mersam sub-district, Batang Hari district. Next, the data collection techniques were analyzed by data reduction, data presentation, and drawing conclusions. The results of this research show that the Kembang Paseban sub-district for managing waqf, especially the Addiniyah Madrasah, is quite good. With the existence of a madrasa in the Kembang Paseban sub-district, the community can enroll their children in the madrasa. Even though it has not fully improved, the existence of this madrasah waqf is a little more able to improve the welfare of the local community. The presence of a community madrasah can open up opportunities for the community to trade at the madrasah.